Design and experiment of corn low damage threshing device based on DEM - Li, Xiaoyu; Du, Yuefeng; Mao, Enrong; Zhang, Yan’an; Liu, Lei; Guo, Dafang (International Journal of Agricultural and Biological Engineering, 2023)
Kernel broken rate is an important index to evaluate the maize kernel direct harvesting quality. In view of the problem of the high kernel broken rate in the present maize harvester, a new threshing cylinder was designed in this study. This device utilized rasp bar to achieve low damaged maize ears threshing. In order to determine the structure and working parameters of threshing device, the "crop-crop" contact model and the "crop-mechanical" interaction system were established and analyzed based on the discrete element method first, and the mathematical expressions of the related kinematic response of maize kernel under the external force were obtained. Then, the structure parameters of rasp bar were studied through EDEM simulation experiment, and the working parameters were determined through test-bed experiment. Finally, the simulation experiment results and test-bed experiment results were verified through field experiment. The results showed that when the threshing cylinder speed was 356 r/min, the concave clearance was 40 mm, the installation distance of rasp bar was 250 mm with 50Mn steel, and the feeding amount was 8 kg/s, the kernel broken rate was 1.93%, which satisfied the requirements of maize harvest standard. This study proved that the DEM (Discrete Element Method) can be adopted to guide the optimization design of mechanical structure, and it has certain value for the research and development of operation equipment of other agricultural crops. Keywords: DEM, maize threshing, low damage harvesting, kernel broken rate, simulation DOI: 10.25165/j.ijabe.20231603.7042 Citation: Li X Y, Du Y F, Mao E R, Zhang Y A, Liu L, Guo D F. Design and experiment of corn low damage threshing device based on DEM. Int J Agric & Biol Eng, 2023; 16(3): 55–63.